Liquid‐Crystal‐Elastomer‐Actuated Reconfigurable Microscale Kirigami Metastructures. Issue 25 (13th May 2021) - Zhang, Mingchao; Shahsavan, Hamed; Guo, Yubing; Pena‐Francesch, Abdon; Zhang, Yingying; Sitti, Metin
Abstract: Programmable actuation of metastructures with predesigned geometrical configurations has recently drawn significant attention in many applications, such as smart structures, medical devices, soft robotics, prosthetics, and wearable devices. Despite remarkable progress in this field, achieving wireless miniaturized reconfigurable metastructures remains a challenge due to the difficult nature of the fabrication and actuation processes at the micrometer scale. Herein, microscale thermo‐responsive reconfigurable metasurfaces using stimuli‐responsive liquid crystal elastomers (LCEs) is fabricated as an artificial muscle for reconfiguring the 2D microscale kirigami structures. Such structures are fabricated via two‐photon polymerization with sub‐micrometer precision. Through rationally designed experiments guided by simulations, the optimal formulation of the LCE artificial muscle is explored and the relationship between shape transformation behaviors and geometrical parameters of the kirigami structures is build. As a proof of concept demonstration, the constructs for temperature‐dependent switching and information encryption is applied. Such reconfigurable kirigami metastructures have significant potential for boosting the fundamental small‐scale metastructure research and the design and fabrication of wireless functional devices, wearables, and soft robots at the microscale as well. Abstract : Programmable and reconfigurable metasurfaces at the microscale are achieved by using uniaxially aligned liquid crystal elastomer film as artificial muscle to thermally actuate kirigami microstructures 3D‐printed via the two‐photon polymerization technique. This strategy paves the way to a host of potential applications, such as tunable phononic/photonic crystals, optoelectronics, biomedical devices, camouflage, microelectromechanical systems, and soft microrobots.